Students’ Response of Teacher’s Written Feedback on Their Writing - Sari, Mardhiyati Ambar (Universitas Islam Negeri Raden Intan Lampung, 2017)
This research conducted based on the phenomena taking place in school were many students considered writing is difficult. The students do not know whether their writing was right or not because the students are also shy to ask the teacher when they found difficulties in writing. In addition, the students are lacking of motivation in learning writing because the class condition was not attractive. The students’ writing score is below the criteria minimum mastery (KKM) at SMAN 7 Bandar Lampung. Therefore, this research discusses the analysis of teacher written feedback in students’ written task and their responses. The objective of the research was to know and to describe the aspects of good teacher written feedback fulfilled by teacher, the teacher obstacles and students respond of written feedback at the second semester of the tenth grade of SMAN 7 Bandar Lampung in the academic year of 2016/2017. This research was qualitative research. The data were analyzed using data reduction, data display and data conclusion. The population of this research was the tenth grade students of SMAN 7 Bandar Lampung. The sample in this research was 32 students that were taken from one class, X IPA 2. In collecting the data, the researcher used instruments, interview, questionnaire and documentation review. From the data analysis, it was found that the result of the analysis test was the teacher hardly ever fulfilled those three aspects completely. Many problems that teacher faced in giving written feedback and the students lack in response of teacher written feedback in students written task in the second semester of the tenth grade at SMAN 7 Bandar Lampung.